2017
DOI: 10.1016/j.bpj.2017.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Drosophila Larval Chordotonal Organ

Abstract: Proprioception is an integral part of the feedback circuit that is essential for locomotion control in all animals. Chordotonal organs perform proprioceptive and other mechanosensory functions in insects and crustaceans. The mechanical properties of these organs are believed to be adapted to the sensory functions, but had not been probed directly. We measured mechanical properties of a particular chordotonal organ-the lateral pentascolopidial (lch5) organ of Drosophila larvae-which plays a key role in proprioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…In the wt larvae, muscle contractions lead to shortening of the cap cell with no apparent change in the length of the ligament cell ( Figures 2C and 2D), suggesting that the ChO elastic response is dominated by the cap cell and the ligament cell acts as a rigid body, in agreement with (Prahlad et al, 2017). This finding is consistent with the observation that most of the elongation of the sensory organ during development is attributed to the cap cell.…”
Section: The Morphology and Mechanical Properties Of The Chordotonal supporting
confidence: 86%
See 1 more Smart Citation
“…In the wt larvae, muscle contractions lead to shortening of the cap cell with no apparent change in the length of the ligament cell ( Figures 2C and 2D), suggesting that the ChO elastic response is dominated by the cap cell and the ligament cell acts as a rigid body, in agreement with (Prahlad et al, 2017). This finding is consistent with the observation that most of the elongation of the sensory organ during development is attributed to the cap cell.…”
Section: The Morphology and Mechanical Properties Of The Chordotonal supporting
confidence: 86%
“…The mechanical probe was positioned next to the center of the cap cell and oscillated in a direction perpendicular to the axis of the cap cell with an amplitude of 25 mm using an Arbitrary function generator (Stanford DS345). A similar setup was used in Prahlad et al (2017).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Superresolution imaging showed that dCirl colocalizes to region with the mechanosensitive channel where it suppresses cAMP levels and increases excitability of ChOs Interestingly, the opsins also seem to have a neuroprotective function, as dendrites lacking NINAE and Rh6 are more flaccid, disorganized and showed increased membrane blebbing than in wildtype flies 65 . These phenotypes are similar to neuromechanical defects seen in C. elegans mechanosensors 68 and it is interesting to speculate whether or not the mechanical pre-stress seen in chordotonal organs 57 70 , DVA interneurons 48,71,72 , the SMD neurons 73 and VA, VB motoneurons 74,75 (Fig. 1E).…”
Section: Insights From Non-vertebrate Model Organismssupporting
confidence: 57%
“…How a mechanical stretch can cause bending of the cilia is a mystery, but active motility was suggested to cause lateral deflection of the ciliary microtubules 56 . Laser cutting of the ChO suggest that the sensory and support cells are under constitutive mechanical tension 57 .…”
Section: Insights From Non-vertebrate Model Organismsmentioning
confidence: 99%
See 1 more Smart Citation